Nieskrytość - Poprawa, Adam (1959- ).; Błoński, Jan (1931-2009). (2004)
Recenzja książki: Listy 1963-1996 / Jan Błoński, Sławomir Mrożek. Kraków, 2004.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.